FERTILITY OF LACTATING JERSEY X HOLSTEIN-FRIESIAN COWS IN SUBTROPICAL REGION SUBMITTED TO A DOUBLE-OVSYNCH VERSUS OVSYNCH PROTOCOL FOR TIMED ARTIFICIAL INSEMINATION - A. A. Channa; M. Aleem; M. A. Jabbar; H. Monir; N. Ahmad1 (Journal of Animal and Plant Sciences, 2020)
Pre-synchronization prior to Ovsynch protocol is an efficient method to improve ovulation and pregnancy rate in dairy cows. The objective of this study was to define the effect of Double-Ovsynch (DOS; GnRH, PGF2α 7 d later and GnRH 2 d later followed by the OVS protocol with interval of 7 d; timed AI 16 to 24 h after the last GnRH of OVS) and Ovsynch (OVS; GnRH, PGF2α 7 d later and GnRH 2 d later; timed AI 16- 24 h after the last GnRH) protocols on ovulation and pregnancy rate in crossbred dairy cows. The ovulation rate (day 7 post TAI, DOS n = 20 vs. OVS n = 21) and pregnancy rate (day 35 post TAI, DOS n = 125 vs. OVS n = 148) were determined using ultrasonography. Serum concentrations of progesterone on d 7 after the last GnRH of each protocol was determined in the subset of randomly selected cows (DOS n = 10) and (OVS n =10) protocol. The Ovulation rate (OR) was higher (P < 0.05) in DOS as compared to OVS (90% vs. 47%) protocols. Likewise, pregnancies per AI (P/AI) significantly (P<0.05) increased in DOS as compared to OVS (62 % vs. 30%). Mean serum concentrations of progesterone on d 7 remained similar (P > 0.05) between DOS and OVS (8.68 ± 0.78 ng/mL: 8.19 ± 1.85 ng/mL)protocols. It is concluded that DOS compared to OVS yields better ovulation and pregnancy rate in crossbred dairy cows.
Keywords: Ovsynch; Double-Ovsynch; Ovulation; Pregnancy; Crossbred cows